This will be an attempt to explain the notation I use to describe the setting of clues and the removal of candidates necessary to solve a Sudoku puzzle. The objective is to provide a method to describe to others a solution that you see. So a notation must be able to communicate or be understood by others. To me that is the only rule.

As an example, the following puzzle can be solved --reduced to singles-- with an xy-wing with pinchers located in r3c8 and r4c4 connected by r4c8 will remove a candidate 2 in r3c4. This will reduce the puzzle to singles.

- Code: Select all
`*-----------------------------------------------------------*`

| 48 58 3 | 7 24 15 | 12 9 6 |

| 46 2 1 | 9 46 8 | 7 5 3 |

| 9 7 56 | 6-2 3 15 | 4 a12 8 |

|-------------------+-------------------+-------------------|

| 3 6 4 |c28 128 9 | 5 b18 7 |

| 128 58 2578 | 4 178 6 | 18 3 9 |

| 18 9 78 | 5 178 3 | 6 4 2 |

|-------------------+-------------------+-------------------|

| 7 3 28 | 1 9 4 | 28 6 5 |

| 5 4 9 | 68 68 2 | 3 7 1 |

| 268 1 268 | 3 5 7 | 9 28 4 |

*-----------------------------------------------------------*

The objective is to prove the removal of 2 in r3c4.

if r3c8 is a 2 then the objective is met.

if r3c8(a) is not a 2 then it has to be 1 this is shown in notation as (2=1)r3c8

with r3c8 a 1 then r4c8(b) must be an 8 adding to our notation we get (2=1)r3c8-(1=8)r4c8

if r4c8 is an 8 then r4c4(c) must be a 2 forcing the removal of a 2 in r3c4 Objective met. our notation becomes (2=1)r3c8-(1=8)r4c8-(8=2)r4c4

Many use the => notation which means "therefore" (2=1)r3c8-(1=8)r4c8-(8=2)r4c4 => -2r3c4

I like to use brackets to show a proof followed by a result.

[(2=1)r3c8-(1=8)r4c8-(8=2)r4c4]-2r3c4

The semicolon represents the end of a step. ste means "singles to end" so we complete our notation with

[(2=1)r3c8-(1=8)r4c8-(8=2)r4c4]-2r3c4; ste

For fun try going backwards starting with if r4c4 is not 2 then....

Comments and further posts are welcome. Maybe we can learn better ways to communicate Sudoku solutions.